Feasibility of a prehabilitation program before major abdominal surgery: a pilot prospective study. Issue 11 (November 2021) - Martin, David; Besson, Cyril; Pache, Basile; Michel, Anna; Geinoz, Sandrine; Gremeaux-Bader, Vincent; Larcinese, Anna; Benaim, Charles; Kayser, Bengt; Demartines, Nicolas; Hübner, Martin
Objective: To assess the feasibility of a prehabilitation program and its effects on physical performance and outcomes after major abdominal surgery. Methods: In this prospective pilot study, patients underwent prehabilitation involving three training sessions per week for 3 weeks preoperatively. The feasibility of delivering the intervention was assessed based on recruitment and adherence to the program. Its impacts on fitness (oxygen uptake (VO2 )) and physical performance (Timed Up and Go Test, 6-Minute Walk Test) were evaluated. Results: From May 2017 to January 2020, 980 patients were identified and 44 (4.5%) were invited to participate. The main obstacles to patient recruitment were insufficient time (<3 weeks) prior to scheduled surgery (n = 276, 28%) and screening failure (n = 312, 32%). Of the 44 patients, 24 (55%) declined to participate, and 20 (23%) were included. Of these, six (30%) were not adherent to the program. Among the remaining 14 patients, VO2 at ventilatory threshold significantly increased from 9.7 to 10.9 mL/min/kg. No significant difference in physical performance was observed before and after prehabilitation. Conclusion: Although prehabilitation seemed to have positive effects on exercise capacity, logistic and patient-related difficulties were encountered. The program is not feasible in its current form for all-comers.